Platelets in Vascular Calcification: A Comprehensive Review of Platelet-Derived Extracellular Vesicles, Protein Interactions, Platelet Function Indices, and their Impact on Cellular Crosstalk - He, Yi; Zhang, Qiongyue; Pan, Lina; Yang, Hao; Liu, Tao; Bei, Junjie; Peter, Karlheinz; Hu, Houyuan (Seminars in Thrombosis and Hemostasis, 2024)
Vascular calcification (VC) commonly accompanies the development of atherosclerosis, defined by the accumulation of calcium in the arterial wall, potentially leading to stroke and myocardial infarction. Severe and unevenly distributed calcification poses challenges for interventional procedures, elevating the risks of vascular dissection, acute vascular occlusion, restenosis, and other major adverse cardiovascular events. Platelets promote the development of atherosclerosis by secreting various inflammatory mediators, regulating cell migration, aggregation, adhesion, and initiating and expanding inflammatory responses. There is emerging evidence that platelets play a direct role in VC; however, this novel concept has not yet been critically assessed. This review describes the intricate mechanisms by which platelets promote VC, focusing on three key aspects and the potential opportunities for their therapeutic targeting: extracellular vesicles, platelet-regulatory proteins, and indices related to platelet function.
Keywords: platelet; vascular calcification; cellular crosstalk; platelet-derived extracellular vesicles; platelet-derived growth factor-BB